2019
DOI: 10.3390/ijms21010225
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analyses Reveal New Insights on the Antimicrobial Mechanisms of Chitosan Biopolymers and Their Nanosized Particles against Escherichia coli

Abstract: The well-known antimicrobial effects of chitosan (CS) polymers make them a promising adjuvant in enhancing antibiotic effectiveness against human pathogens. However, molecular CS antimicrobial mechanisms remain unclear, despite the insights presented in the literature. Thus, the aim of the present study was to depict the molecular effects implicated in the interaction of low or medium molecular mass CS polymers and their nanoparticle-counterparts against Escherichia coli. The differential E. coli proteomes sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Other factors related to chitosan antimicrobial activity are the absorbing property of metal ions and their ease of penetrating the cell wall and binding to DNA, inhibiting messenger RNA synthesis, and low molecular weight of chitosan molecule induced inhibition of DNA transcription and mRNA synthesis in E. coli [ 110 , 111 , 112 , 113 , 114 , 115 ].…”
Section: Chitin and Chitosan Applicationsmentioning
confidence: 99%
“…Other factors related to chitosan antimicrobial activity are the absorbing property of metal ions and their ease of penetrating the cell wall and binding to DNA, inhibiting messenger RNA synthesis, and low molecular weight of chitosan molecule induced inhibition of DNA transcription and mRNA synthesis in E. coli [ 110 , 111 , 112 , 113 , 114 , 115 ].…”
Section: Chitin and Chitosan Applicationsmentioning
confidence: 99%
“…Low-molecular-weight chitosan oligomers pass through the cell membrane and alter cell permeability [37]. Nanochitosans have been shown to disassemble bacteria cell membranes and inhibit metabolic and biosynthetic pathways [38].…”
Section: Chemical Modifications On Chitin and Chitosan Surfaces: Deve...mentioning
confidence: 99%
“…Resveratrol owes its antioxidant activity to its phenolic hydroxyl groups and can be used to achieve oxidative skin cell homeostasis following topic use or aid in the fight against chronic and degenerative human physiopathological conditions by promoting organism oxidative balance when administered systemically as a nutraceutical or pharmaceutical [43]. Chitosans also exhibit well-documented antimicrobial activities against Gram-positive and Gram-negative bacteria and fungi [38,53]. However, due to its low solubility, antimicrobial activity is limited to acidic media, although antimicrobial activity in neutral media can be improved by transforming amino groups into quaternary ammonium salts (NR4 + X − ) [54].…”
Section: Chemical Modifications On Chitin and Chitosan Surfaces: Deve...mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Studies have shown that chitosan binding to lipopolysaccharides on the bacterial surface disrupts the order of the bacterial membrane and causes the plasma to leak out. 16 It also increases the chances of drug penetration into the bacterial cytoplasm. 17 In this study, aqueous and methanolic extracts were obtained from ginger root individually, and then CHI nanoparticles (NPs) containing each extract were prepared.…”
Section: Introductionmentioning
confidence: 99%